TYPES AND ABUNDANCE OF MARINE DEBRIS IN THE CORAL REEF ECOSYSTEM OF PASUMPAHAN ISLAND, WEST SUMATRA - Hanifah, Lulu Lyana; Amin, Bintal; Nasution, Syafruddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Debris has long been a worrying problem, especially in the marine environment. Human activities and marine tourism activities cause coral reef ecosystem damage. The research was carried out in June - September 2022 to determine the type and abundance of marine debris, lifeforms, and condition of coral cover, as well as the relationship between the abundance of marine debris and coral cover on Pasumpahan Island, West Sumatra. The research method used was a survey, and the data obtained was analyzed descriptively. The research location was divided into three observation stations by placing three transects at each station. Based on the research results, six types of marine waste were found, with abundance ranging from 0.01 to 0.085 units/m2. The coral lifeforms found are Acropora branching, Acropora encrusting, Acropora submassive, Coral encrusting, Coral foliose, Coral millepora, Coral mushroom, and Coral massive, with a percentage of live coral cover ranging from 1.00-36.48%. A strong negative relationship exists between the abundance of marine debris and the percentage of coral cover in Pasumpahan Island, West Sumatra